Supramolecular control over pH- and temperature-responsive dialkoxynaphthalene-functionalized poly(2-(dimethylamino)ethyl methacrylate) in water. (5th April 2021) - Coumes, Fanny; Le Fer, Gaëlle; Malfait, Aurélie; Hoogenboom, Richard; Fournier, David; Woisel, Patrice
Graphical abstract: Abstract: In the framework of the development of multi-responsive polymer materials, a well-defined copolymer bearing supramolecular recognition units was designed based on 2-(dimethylamino)ethyl methacrylate (DMAEMA) and a dialkoxynaphthalene-functionalized monomer (NaphtA). The supramolecular host–guest interactions of this P(DMAEMA- co -NaphtA) copolymer with the electron-deficient CBPQT 4+, 4Cl - cyclophane host were studied by 1 H NMR spectroscopy, UV–Visible spectroscopy and isothermal titration calorimetry (ITC), revealing, a high association constant of 6.5 × 10 5 M −1 in water. The addition of CBPQT 4+, 4Cl - to a colorless solution of the copolymer in water resulted in a purple solution due to the formation of donor–acceptor inclusion complexes, the intensity being directly proportional to the amount of host added. Investigations on the thermoresponsive behavior of the naphthalene-functionalized copolymer highlighted that the cloud point temperature is directly proportional to the amount of CBPQT 4+, 4Cl - host added and can simply be programmed within a temperature window from 30 °C to 48 °C by playing with pH. The dethreading process was studied as function of temperature and anionic exchange of the counterions of the CBPQT 4+, 4Cl - . Interestingly, a partial decomplexation was observed by heating the sample above the cloud point temperature while a complete and programmable dethreading was achieved by adding the anionic surfactant sodium dodecyl sulfate (SDS) as a competitive counterion of the host molecule.